2020
DOI: 10.1155/2020/1586707
|View full text |Cite
|
Sign up to set email alerts
|

Psoas Muscle Area Measured with Computed Tomography at Admission to Intensive Care Unit: Prediction of In-Hospital Mortality in Patients with Pulmonary Embolism

Abstract: Aim. Sarcopenia, a core component of physical frailty, is an independent risk factor for suboptimal health outcomes in hospitalized patients, especially in the intensive care patients. Psoas muscle areas can be assessed to identify sarcopenia. The aim of this study was to determine the prognostic value of psoas muscle area measured with CT for the prediction of in-hospital mortality in patients with pulmonary embolism at admission to the intensive care unit. Methods. Patients with an admission abdominal comput… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
26
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(28 citation statements)
references
References 34 publications
(34 reference statements)
2
26
0
Order By: Relevance
“…In addition, DEXA is not feasible at the bedside and involves patient radiation exposure. Computed tomography (CT) has been recently used to assess muscle mass and its correlation with mortality in critically ill patients (16). Despite its excellent accuracy, CT is expensive, FIGURE 2 | Probability of discharge (dot green line) and of transferal to rehabilitation unit (solid red line) according to the degree of muscle wasting (x-axis).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, DEXA is not feasible at the bedside and involves patient radiation exposure. Computed tomography (CT) has been recently used to assess muscle mass and its correlation with mortality in critically ill patients (16). Despite its excellent accuracy, CT is expensive, FIGURE 2 | Probability of discharge (dot green line) and of transferal to rehabilitation unit (solid red line) according to the degree of muscle wasting (x-axis).…”
Section: Discussionmentioning
confidence: 99%
“…(21) Among these, the PMA determined using CT is the most widely accepted tool for diagnosing sarcopenia (1,2,(12)(13)(14)(15), as PMA has been indicated to be the most powerful predictor of hospital stay among other parameters including lumbar muscle area, and thoracic muscle area. (21,22) Previous research indicates that preoperative sarcopenia defined using PMA was associated with poorer long-term outcomes after valve surgery through full sternotomy. (1,2,23) Sarcopenia can be used as one of the objective means for defining frailty (11), and the surgical outcomes of patients with frailty are inevitably poor.…”
Section: (Video 1)mentioning
confidence: 99%
“…Fifth, there is debate regarding the level at which the psoas area should be measured, with some authors using L4 as the reference level 42 . We measured at L3 given that skeletal muscle area has been reported to peak at this level 16 and L3 measurements are more commonly reported in the literature 8,43 . Sixth, freehand planimetry has the disadvantage of including intramuscular fat as part of the measured muscle area.…”
Section: Limitationsmentioning
confidence: 99%
“…A validated method for quantifying sarcopenia is the measurement of psoas muscle area using cross-sectional computed tomography (CT) imaging 5 . Using psoas area as a surrogate measure, previous studies have demonstrated an association between sarcopenia and morbidity/mortality in patients with abdominal aortic aneurysm 6 , colorectal cancer 7 , and pulmonary embolism 8 . However, the literature on sarcopenia in patients undergoing TAVI is heterogenous in terms of the measurement of sarcopenia, with prevalence ranging from 21% -70% based on definitions used 9 .…”
Section: Introductionmentioning
confidence: 99%